Approach to the Multimedia-Based Contextual Learning of Arabic for Banking - Beti Mulu; Masdin Masdin; Wa Muna; Isna Humaera; Samrin Samrin (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2022)
This study aims to reveal the motivation to learn Arabic for the banking sector through multimedia-based contextual learning using qualitative methods. Data were garnered using observation, interviews, and documents. The results of data analysis show that contextual learning can motivate students to learn and play an active role in formulating the contextual conversation according to the theme given to each group. The students' attention was focused on searching vocabulary, asking questions, and completing the script in the allotted time. They were diligent, tenacious and enthusiastic in role playing the conversational texts and practicing speaking and acting using Arabic for banking conversation scripts.Keywords: Arabic for banking; contextual teaching and learning; multimedia